Case Report: Anti-flotillin 1/2 Autoantibody-Associated Atypical Dementia - Hansen, Niels; Bartels, Claudia; Stöcker, Winfried; Wiltfang, Jens; Timäus, Charles (Frontiers in Psychiatry, 2021)
Flotillin proteins are involved in neurodegeneration and T-cell immunity. Here, we report the case of 65-year-old woman who presented with dementia, depressive symptoms, and a patient history involving speech problems. As diagnostics methods we applied magnetic resonance imaging, clinical examination, extensive neuropsychological testing and cerebrospinal fluid analysis. Neuropsychological testing revealed major cognitive decline in attentional, executive and memory functions together with impaired activities of daily living. The cerebrospinal fluid showed elevated phosphorylated tau protein 181. We identified serum autoantibodies against the flotillin 1 /2 complex. Immunotherapy entailing four cycles of high-dose steroids resulted in less cognitive dysfunction along with reduced depressive symptoms in the second follow-up after starting steroids. In conclusion: probable autoimmune-mediated dementia associated with anti-flotillin 1/ 2 complex autoantibodies expands the phenotypic spectrum of anti-flotillin 1/2 antibody disease.